Aicardi syndrome, an unsolved mystery: Review of diagnostic features, previous attempts, and future opportunities for genetic examination. Issue 4 (10th December 2018) - Wong, Bibiana K. Y.; Sutton, V. Reid
Abstract: Aicardi syndrome is a rare, severe neurodevelopmental disorder classically characterized by the triad of infantile spasms, central chorioretinal lacunae, and agenesis of the corpus callosum. Aicardi syndrome only affects females, with the exception of a few males with a 47, XXY chromosome constitution. All cases are de novo and the only cases of definitive recurrence in families are in identical twins. It is now recognized that individuals with Aicardi syndrome commonly exhibit a variety of other neuronal migration defects, eye anomalies, and other somatic features, including skin, skeletal, and craniofacial systems. The etiology of Aicardi syndrome remains unknown despite an international effort exploring different genetic mechanisms. Although various technologies examining candidate genes, copy number variation, skewing of X‐chromosome inactivation, and whole‐exome sequences have been explored, no strong genetic candidates have been identified to date. New technologies that can detect low‐level mosaicism and balanced rearrangements, as well as platforms examining changes at the DNA and chromatin level affecting regulatory regions are all potential avenues for future studies that may one day solve the mystery of the etiology of Aicardi syndrome.